2007
DOI: 10.1002/jsfa.3060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breed type, housing and feeding system on performance of growing pigs managed under organic conditions

Abstract: BACKGROUND: There is a need for information on the performance and carcass quality of pigs under different organic management systems. This study compared Duroc-sired progeny from three maternal breed types when kept either at pasture or in housing with an outdoor run and offered ad libitum concentrate either alone or with fodder beet or grass/clover silage as additional forage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 18 publications
(13 reference statements)
2
10
0
1
Order By: Relevance
“…Concerning carcass quality (Figure 3), the old breeds (AS and SH) show their low potential in lean meat percentage, Figure 3 Differences of lean meat in the carcass grouped for genotype and environment (least square mean). Brandt, Werner, Baulain, Brade and Weissmann which is according to the other findings (Kelly et al, 2007). The inferiority is obvious under both systems.…”
Section: Resultssupporting
confidence: 73%
“…Concerning carcass quality (Figure 3), the old breeds (AS and SH) show their low potential in lean meat percentage, Figure 3 Differences of lean meat in the carcass grouped for genotype and environment (least square mean). Brandt, Werner, Baulain, Brade and Weissmann which is according to the other findings (Kelly et al, 2007). The inferiority is obvious under both systems.…”
Section: Resultssupporting
confidence: 73%
“…However, Werner et al (2007) found significant GxE interactions when Livestock Science 123 (2009) 154-160 investigating growth rate and carcass leanness in seven different breeds and breed-crosses in organic and conventional environments. Kelly et al (2007) found no significant GxE interactions when comparing a traditional breed, a modern breed, and a cross between the two, in outdoor and indoor organic environments.…”
Section: Introductionmentioning
confidence: 71%
“…Otherwise, traits for indoor organic production are largely similar to outdoor production, including maternal abilities, piglet vitality and sow longevity. Next to desirable traits of breeds for organic production, Kelly et al (2007) concluded that the choice of breed should also depend on the ability of the herd to manage prolific sows. Therefore, based on results of this study, the choice for a Yorkshire sow line either as part of a cross in OrgBS and RotBS or as a purebred line in FlowerBS, might be a good option for the Dutch organic sector, provided that organic farmers are able to handle the larger litters that this line produces.…”
Section: Discussionmentioning
confidence: 99%